How does changing technology affect students note-taking - Alsulmi, Badria (Kansas State University, 2012)
In recent years, technology has improved and become a significant aspect in the classroom. Using technology has become a popular method of note-taking. This study investigates the effects of technology on note-taking by looking at the changes that can be shown between the traditional note-taking and taking notes by using different devices, such as the iPad and a smart pen. Modern technology, such as the smart pen which provides an automatic audio recording might improve student focus on important details. In addition, providing a standard note set along with note-taking tools such as an iPad might help student organize and access their notes. The result of this study showed that for all but one of the students, using technology did not affect their note-taking style or the amount of information in their notes. However, students were not satisfied with their notes when taken on the iPad.
Keywords: Note-taking; Smart Pen; iPad; Mathematics (0405)